Effect of physical exercise on sleep quality of college students: Chain intermediary effect of mindfulness and ruminative thinking - Ye, Jun; Jia, Xuemei; Zhang, Junjie; Guo, Kelei (Frontiers in Psychology, 2022)
Physical Exercise Scale, Mindfulness Attention Awareness Scale (MAAS), Ruminative Thinking Scale (RRS) and Pittsburgh Sleep Quality Index (PSQI) are applied to conduct the questionnaire among 1006 college students (average age=19.95 years, SD=1.86 years) to figure out whether there is any correlation between physical exercise and college students' sleep quality as well as how the mechanism of mindfulness and ruminative thinking play a factor in them. For data analysis, Harman single factor test was used for common method deviation test, Pearson’s correlation analysis, and the mediating effect tested by Bootstrap method were carried out in turn. Results: (1) 34% (PSQI ≥ 8) of college students' sleep quality are poor. (2) PSQI is positively correlated with ruminative thinking, while both are negatively correlated with level of physical exercise and mindfulness; level of physical exercise is positively correlated with level of mindfulness. (3) physical exercise can significantly negatively predict sleep quality(β=-0.08,P<0.05); Significant positive predictive mindfulness（β=0.12,P<0.001）； Significant negative prediction rumination（β=-0.07,P<0.05）; When participate in physical exercise, mindfulness and rumination enter the regression equation at the same time, only mindfulness and rumination can predict sleep quality（β=-0.15,P<0.001) significantly negatively predicted sleep quality and rumination（β=0.22,P<0.001) significantly positively predicted sleep quality, while physical exercise（β=-0.04,P>0.05) had no significant predictive effect on sleep quality. (4) After controlling age and gender, physical exercise appears an impact on college students' sleep quality through the independent intermediary role of mindfulness and ruminative thinking and the chain intermediary role of mindfulness and ruminative thinking, with a total mediating effect value of -0.007. This study reveals the relationship between physical exercise and sleep quality as well as its mechanism, so as to guide college students to actively participate in physical exercise. The study also provides corresponding suggestions to improve college students' sleep quality as well as physical and mental health.